Hadith #332 - Sahih al-Bukhari - 'Urwa's father (Sahih al-Bukhari)
Aisha said, “I borrowed a necklace from Asma’ and it was lost. So Allah’s Messenger (ﷺ) sent a man to search for it and he found it. Then the time of the prayer became due and there was no water. They prayed (without ablution) and informed Allah’s Messenger (ﷺ) about it, so the verse of Tayammum was revealed.” Usaid bin Hudair said to `Aisha, “May Allah reward you. By Allah, whenever anything happened which you did not like, Allah brought good for you and for the Muslims in that.
Grade: Sahih

Hadith #380 - Sahih al-Bukhari - 'Urwa's father (Sahih al-Bukhari)
The Prophet (ﷺ) prayed while `Aisha was lying between him and his Qibla on the bed on which they used to sleep.
Grade: Sahih